Targeted temperature management in patients undergoing extracorporeal life support after out-of-hospital cardiac arrest: an EURO-ELSO 2018 annual conference survey. (November 2019) - Rolfes, Caroline; Muellenbach, Ralf M; Lepper, Philipp M; Spangenberg, Tobias; Swol, Justyna; Lorusso, Roberto; Weber, Klaus; Foerstner, Sarina; Lotz, Christopher; Belohlavek, Jan
Targeted temperature management and extracorporeal life support, particularly extracorporeal membrane oxygenation in patients undergoing cardiopulmonary resuscitation, represent outcome-enhancing strategies for patients following in- and out-of-hospital cardiac arrest. Although targeted temperature management with hypothermia between 32°C and 34°C and extracorporeal cardiopulmonary resuscitation bear separate potentials to improve outcome after out-of-hospital cardiac arrest, each is associated with bleeding risk and risk of infection. Whether the combination imposes excessive risk on patients is, however, unknown.